The Process and Barriers in Computer-Mediated Communication (A Case Study of Indonesian and Australian Students' Collaboration Project) - Selvi Siregar; Carly Stiana Scheffer-Sumampouw (Jurnal Studi Komunikasi dan Media, 2021)
This paper describes how university students from diverse cultural background and separated by geographical distance conduct communication process using computer-mediated communication (CMC). The purpose of our research is to examine the communication process and identify potential barriers that can disturb the collaboration. We also aim to find which cultural dimensions influence the communication process. The population is 15 Journalism students from UPH, Indonesia and 15 Journalism students from QUT, Australia who joined a collaboration project from October – November 2018. We use a qualitative case-study, with analytical descriptive method. We analyze multiple sources of evidence such as: logbook and recorded correspondence, Focus Group Discussions (FGD) and depth interview for data collection. Results show the students use mostly asynchronous communication such as chat text and Google Docs for their communication medium. The main barriers are language proficiency and slow internet connections. This study analyzes one case study involving students from two different nations. We find that Individualism, Masculinity and Power Distance cultural dimensions influence how they communicate to each other.